HUBUNGAN PENGETAHUAN IBU TENTANG BUKU KIA DENGAN KEJADIAN STUNTING PADA BALITA DI WILAYAH PUSKESMAS TABUNGANEN - Elyani, Elyani; Zakiah , Hj.; Yuliastuti , Erni; Laili , Fitria Jannatul (Seroja Husada: Jurnal Kesehatan Masyarakat, 2025)
Background: In 2024, stunting prevalence in Barito Kuala Regency reached 11.07%, potentially linked to suboptimal use of the Maternal and Child Health (MCH) Book. This is reflected in low first neonatal visits (70.3%), complete neonatal visits (69.2%), limited child health service coverage (79%), and infant and toddler mortality rates (1.2%).Methods: This quantitative cross-sectional study involved 98 mothers of toddlers aged 24–59 months in the Tabunganen Health Centre area. Data were collected through questionnaires and nutritional assessments, then analysed using Chi-Square and Odds Ratio tests..Results: The majority of mothers (55.1%) had good knowledge of the MCH Book, while stunting prevalence among toddlers was 45.9%. A significant association was found between maternal knowledge of the MCH Book and stunting (p=0.000), with mothers lacking knowledge showing a higher risk of having stunted children (OR > 1).Conclusion: A significant association was found between maternal knowledge of the MCH Book and stunting, with limited knowledge increasing the risk of stunting in toddlers.Recommendations: Strengthen health education for mothers on the use and benefits of the Maternal and Child Health Book through collaboration among healthcare providers, community leaders, and local health authorities as a key strategy for early stunting prevention.